The historical starting points for the statehood of umayyad caliphate - Ahmed Jabar Jamr al-Hilali, Saad Kadhim Abd Al-Janabi, (Opción, 2019)
This research aims at studying the factors of the establishment of the Umayyad caliphate through the history of Al-Tabari (The History of the Prophets and Kings) who has passed away in 310 A.H, through comparing his stories with the other Islamic history resources. As a result, some of the historians who preceded Al-Tabari agreed that Abu Bakr made Yazid the Caliph of Syria in order to create the Umayyad caliphate. In conclusion, the killing of Ali bin Abi Talib is among the most important factors that precipitated the establishment of the Umayyad Caliphate.